General Reports of the XVIIIth Congress of the International Academy of Comparative Law/Rapports Généraux du XVIIIème Congrès de l’Académie Internationale de Droit Comparé - Brown, Karen B.; Snyder, David V. (SpringerLink Bücher, 2012)
David V. Snyder